If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16+3x=36+5x
We move all terms to the left:
16+3x-(36+5x)=0
We add all the numbers together, and all the variables
3x-(5x+36)+16=0
We get rid of parentheses
3x-5x-36+16=0
We add all the numbers together, and all the variables
-2x-20=0
We move all terms containing x to the left, all other terms to the right
-2x=20
x=20/-2
x=-10
| (7x7)+10=(7x9) | | 5x+429=8 | | 31-2z=5(z-5) | | 25.1+5y=8y+17 | | 9x-10=10x-3 | | 5w+10=6w+15 | | 7v+8=3v+28 | | d/9=21/2 | | 2u+30=7u-15 | | 8=2(h-2) | | 6x3-4=29 | | 2(4g-8)=28 | | 16=44-4f | | 32-4c=16 | | 3+3a=5 | | 7n-7=6 | | 46m+11-33m=(-28) | | 3=6÷1x | | 3=6÷x | | x÷-2=147 | | 1x÷6=7 | | 6x+7−−−−−√=−16x+7=-1 | | (-9f-2)(-7f+7)(-4f-6)=0 | | 15x-9=9x | | x(x-1)=120 | | 0.04+0.06(1200-x)=62 | | 18-6x=96 | | 2x=28+12 | | x-400=25x | | 448(0.75^x^-1)=125 | | 448(0.75^x-1)=125 | | 3(a+1)=9+10 |